Relationship between Long Time Undergoing Hemodialysis and the Level of Sexual Dysfunction in Chronic Renal Failure (CRF) Patients in the Hospital Hemodialisation Unit - Purwandari, Nila Putri; Retnowati, Dewi; Faidah, Noor; Putri, Devi Setya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hemodialysis has negative impacts on patients. The duration of hemodialysis can affect the level of sexual dysfunction in patients with chronic renal failure. Sexual dysfunction is a disorder that occurs in patients undergoing hemodialysis. This disorder often occurs due to decreased productivity, decreased libido, impotence, infertility, genicomasty and neurohormonal disorders. This study aims to determine the relationship between the duration of hemodialysis and the level of sexual dysfunction in patients with chronic renal failure in the hemodialysis unit of the Sunan Kudus Islamic Hospital. This study is a correlational analytical study, with a cross-sectional research design, the sampling method using consecutive sampling, with a sample size of 38 respondents and data collection using a questionnaire. The results of this study showed that with male respondents with a level of severe ED category dysfunction as many as 15 people (39%) in women experiencing sexual dysfunction as many as 14 people (36.8%). The results of the analysis with the Spearman rank correlation test obtained a ρ value of 0.00 <α (0.05) which can be concluded that there is a relationship between the length of hemodialysis and the level of sexual dysfunction in chronic kidney failure (CKF) patients in the Hemodialysis Unit of the Sunan Kudus Islamic Hospital. There is a significant relationship between the length of hemodialysis and the level of sexual dysfunction in chronic kidney failure (CKF) patients at the Hemodialysis Unit of Sunan Kudus Islamic Hospital.